Configuring Audiences: A Case Study of Email Communication - Zhang, Justine; Pennebaker, James W.; Dumais, Susan; Horvitz, Eric (ACM, 2020)
When people communicate with each other, their choice of what to say is tied to their perceptions of the audience. For many communication channels, people have some ability to explicitly specify their audience members and the different roles they can play. While existing accounts of communication behavior have largely focused on how people tailor the content of their messages, we focus on the configuring of the audience as a complementary family of decisions in communication. We formulate a general description of audience configuration choices, highlighting key aspects of the audience that people could configure to reflect a range of communicative goals. We then illustrate these ideas via a case study of email usage—a realistic domain where audience configuration choices are particularly fine-grained and explicit in how email senders fill the To and Cc address fields. In a large collection of enterprise emails, we explore how people configure their audiences, finding salient patterns relating a sender’s choice of configuration to the types of participants in the email exchange, the content of the message, and the nature of the subsequent interactions. Our formulation and findings show how analyzing audience configurations can enrich and extend existing accounts of communication behavior, and frame research directions on audience configuration decisions in communication and collaboration.